Molecular and functional characterization of the role of the histone methyltransferase SETDB1 in malignant melanoma - Federico, Aniello (2019)
Malignant melanoma is the most deadly skin cancer. Clinical studies reported a dramatic increase in the incidence of melanoma over the past few years. A very distinctive feature of melanoma is its high degree of heterogeneity and cellular plasticity. Within the tumor there are different genetically defined subpopulations of melanoma cells, which is one of the reasons for the low efficacy of targeted therapies. Furthermore, most melanomas quickly develop a resistance to these therapies, causing tumor relapse. For all these reasons, gaining an understanding of the molecular and cellular mechanisms driving melanoma progression will be important for developing potent therapeutic approaches. So far, some key regulatory pathways normally activated in melanoma have been well defined, and these pathways are mainly driven by activation of oncogenes like BRAF and NRAS, with a considerable relevance for clinical practice. However, the identification of novel key regulators and pathways is still a challenge and will help to better understand melanoma development and to open up new possibilities to treat therapy resistant tumors. Recent studies and work previously conducted in our laboratory reported that the histone methyltransferase SETDB1 plays a major role in melanoma pathogenesis. It has been observed that SETDB1 expression, which correlates with its amplification state in melanoma, is also associated with melanoma progression. However, the role of SETDB1 and its mode of action in melanoma are still unclear. The aim of this project is to clarify the role of SETDB1 in melanoma, through the identification and functional characterization of SETDB1-mediated molecular mechanisms. Here, I report that SETDB1 expression caused deep changes in melanoma transcriptome resulting in the deregulation of pro- and anti-tumorigenic factors. Specifically, SETDB1 induced THBS1 upregulation and suppressed DCT expression. SETDB1 functions are dependent on its catalytic SET domain. During melanoma progression, SETDB1 promoted important epigenetic alterations such as changing the genomic distribution of H3K9me3 and H3K4me1 marks. These histone 2 modifications impacted the transcription of SETDB1 downstream targets. I could show that melanoma cells were sensitive to treatment with the SETDB1-inhibitor mithramycin A. Mithramycin treatment suppressed SETDB1 expression and tumorigenic properties of melanoma cells. Combinatorial treatment with mithramycin and MAPK inhibitors showed enhanced anti-tumor effects. Taken together, the findings presented here highlight the crucial functional and mechanistic role of SETDB1 in melanoma. SETDB1 could be considered as a potential future target for the treatment of melanoma.
Keywords: Hochschulschrift